The University as a Platform for Discussions on the Ethical Aspect of Researchers' Creativity - Korobko, Margaryta (Ukrainian Cultural Studies, 2023)
Creativity is very important for scientists, but, unfortunately, it rarely becomes a topic for discussion within the field of professional ethics of scientists, engineers, physicists, and other figures in science and technology. After all, creativity is often considered a prerogative of artists only, and in this aspect, the moral side of creativity is practically not discussed. The purpose of the article is to show the importance of the moral aspect of  creativity  and  the  role  of  the  university  in  understanding  this.  General  scientific  methods  were  used  in  the  article:  analytical,  comparative,  and generalization.  Common  from  a  public  perspective  is  to  think  about  science  and  technology  in  terms  of  the  pervasive  and  ubiquitous  practical  impact of scientific achievements: electrification, cars, airplanes, water supply, computers, etc. However, to assess the societal impact of science and technology we cannot neglect the moral importance of scientific knowledge itself and the personal commitments of scientists, engineers, and other  science-oriented  professionals.  Personal  commitments  and  ideals  include  humanitarian,  environmental,  religious,  political,  aesthetic,  and  family obligations. They also include voluntary commitments to adhere the professional standards, especially when these commitments are related to a  person's  broader  value  perspective.  The  university  promotes  not  only  the  development  of  scientific  creativity  among  students  but  also  an  opportunity to understand the moral problems of their professional activities and obtain possible solutions to these problems in professional and corporate ethics courses. Thus, the university helps students in their future activities as the first platform for discussions on the ethical aspect of researchers' work.
Keywords: Creativity; creative skills; professional ethics; ethics of science; scientific creativity